Leadership Ethics in Islam - Prasojo, Muhammad Imam; Athallah, Naufal (Indo Consultan Energi, 2025)
Leadership is a central aspect of managing society and organizations. In the context of Islam, leadership encompasses not only administrative responsibilities but also encompasses moral and spiritual values derived from the Qur'an. This study aims to examine the ethics of leadership from an Islamic perspective, emphasizing the ideal characteristics of a leader as outlined in the teachings of the Qur'an. This study employs a qualitative method with a literature-based approach, in which various Islamic texts and primary sources are analyzed in depth. The results of the study show that Islamic leadership emphasizes values ​​such as trustworthiness, fairness, honesty, deliberation, and responsibility. An ideal leader in Islam is not only oriented toward achieving organizational goals but also has a commitment to social justice and the welfare of the people. The implications of this study suggest that applying the principles of Islamic leadership ethics can provide a crucial foundation for creating governance with integrity and justice in various areas of life.